Kondisi Sosial Ekonomi Petani di Sekitar PT. Palma Megah Mulia (Studi Kasus Kecamatan Jelimpo, Kabupaten Landak) - Rosari, Mira; Hutajulu, Josua Parulian; Suharyani, Anita (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Coconut Oil Palm is the largest plantation subsector developer in Indonesia. One of the palm oil companies in West Kalimantan is PT. Pal. The existence of this company has a significant impact on the social and economic conditions of the population. However, despite this, Kersik Blantian Village, which is the closest village to the company, is still classified as a disadvantaged village. The sample in this research consisted of 25 farmers selected using non-probability sampling techniques, which were then analyzed descriptively. The research results show that PT. Palma Megah Mulia influences the socio-economic conditions of farmers in Kersik Blantian Village. Social conditions influence the improvement of the local economy, community welfare, and economic independence. Meanwhile, economic conditions have an effect on increasing household income, reducing economic inequality, and improving the quality of life.